Structured on-the-job training : unleashing employee expertise in the workplace - Jacobs, Ronald L. (Publication in the Berrett-Koehler organizational performance series., 1995)
Guidelines for setting up training programmes in the work setting since up to 80% of employees job knowledge is gained on-the-job. OJT (on-the- job training).